The Use of Management Information System Direct Procurement (SIMPEL) in the Procurement of Goods and Services within the Ministry of Education, Culture, Research, and Technology - Setyo Yuwono; Gregorius N. Masdjojo (Management Analysis Journal, 2023)
The research objective is to identify and analyze the effect of performance expectancy, effort expectancy, and social influence on behavior intention within the Ministry of Education, Culture, Research, and Technology. To find out and analyze the effect of facilitating conditions and behavior intention on user behavior within the Ministry of Education, Culture, Research, and Technology. The research population is SIMPeL users within the Ministry of Education, Culture, Research, and Technology, totaling 60 people. The sampling technique with census sampling technique is to determine the number of samples by taking all members of the existing population to be sampled so that the sample size is 60 respondents. The data used is primary data in the form of a questionnaire. Data analysis used linear regression analysis. The results of the performance expectancy research have a positive and significant effect on behavior intention. Effort expectancy has a positive and significant effect on behavior intention. Social influence has a positive and significant effect on behavior intention. Facilitating conditions have a positive and significant effect on user behavior. The behavioral intention has a positive and significant effect on user behavior. Behavioral intention does not mediate the influence between performance expectancy on behavioral use. Behavioral intention mediates the influence between effort expectancy on behavioral use. Behavioral intention mediates the influence between social influence on behavioral use.